Perception and Practices Regarding Food Safety and Health Profiles of College Students - Purnasari, Nurwulan; Rusdan, Ilzamha Hadijah (Journal of Agri-Food Science and Technology, 2020)
College students are among the educated parts of urban society and might be considered more resistant to food-borne illness due to higher immune function. The objective of this research was to assess the perceptions and practices of food hygiene among college students and determine their health profile. The method was using a structured questionnaire by cross-sectional survey on 222 college students in Central Java. The descriptive analysis used to describe their perception and food hygiene practices. The study found that more than 90% of participants tended to follow recommended food safety practices. More than 80% of college students reported consumption of potentially hazardous foods, while 36% and 26% reported experience of fever and diarrhea, respectivelyThese findings suggest that specific subsets of the student population are more likely to follow recommended food safety practices and are at lower risk of developing foodborne illnesses. This study will perform the next level analysis, which includes the profile of the gut microbiota.